DRAMA MUSIKAL UNTUK MENGEMBANGKAN KREATIVITAS DAN ANTUSIASME ANAK BERKEBUTUHAN KHUSUS - Nazihah, Wafiqotin; Anggraini, Purwati (Universitas Pendidikan Indonesia, 2020)
Children with special needs are still considered troublesome children for some people, this child has physical and mental limitations and an abnormal mindset like other children, so this makes them marginalized. Whereas the history of human life actually revelas that many Children with special needs have advantages, works of art produced by children have high values, so it needs support and encouragement from the people closest to be able develop their talents.Â Research on children ia focused on creativity and enthusiasm by using qualitative research methods to describe the overall abilities that Children with special needs can realize with detailed descriptions.The research objective is to describe the potential of children through musical drama, in musical drama not only singing but also collaborating dubbing, dancing, music, and acting as well as being holistic, able to show all the abilities of children in on appearance. The results showed taht musical drama is able to make Children with special needs more sensitive to their environment, because the stimulation of the implementation of musical drama exercises results in changes in body movements and emotions of children while learning musical drama is very influential on creativity and antusiasm anak berkebutuhan khusus. Â